Study of the value of project stage-gates within a nuclear power plant - Gumede, Nomfusi (Department of Construction Economics and Management, 2017)
Background: Project Management has become a key activity in most organisations. Organisations are investing increasing resources in projects such as new product development, process improvement, or building new services. This research study has been conducted at a nuclear power plant and it explores the value of project stage-gates within a nuclear power plant. Research Purpose: To identify areas for improvement within the stage-gate review process within Nuclear Project Management. Research Objectives: The research study has considered the following research objectives: determining stagegate review process drivers; establishing the value obtained from the stage-gate review process; determining the impact of not conducting PLCM stage-gate reviews. Research Methodology: A qualitative approach was pursued with a survey questionnaire administered to sample and follow up interviews conducted with the same sample population. A questionnaire and interviews have been conducted with Project Managers (PMs) of the power plant to collect qualitative information about the stage-gate review process. Data has been analysed, interpreted and recommendations have been made. Research Findings: The research findings show that there is a general understanding of the stage-gate review definition; performing stage-gate reviews; purpose of the stage-gate and stage-gate drivers. However, this research study revealed that there are some gaps and little understanding regarding the benefits of the stagegate review process; impact of not conducting stage-gate reviews; stage-gate effectiveness and stage-gate monitoring. Therefore, there are various factors that need to be rectified to enhance the effective implementation of the stage-gate review process. Research Limitations: The research study focused on the projects run within the nuclear projects department, in order to simplify the data collection process. Strategic information that was deemed as sensitive or confidential could not be revealed explicitly during the course of data gathering and therefore inferences had to be made.